PENERAPAN MODEL PEMBELAJARAN COOPERATIF TALKING CHIPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM SARAF DI KELAS XI SMA NEGERI 3 SUSUA - Ferinahati Laia (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
This research aims to improve learning outcomes by applying the Cooperative Talking Chips learning model to nervous system material in class XI SMA Negeri 3 Susua. This research uses quantitative research methods with a Classroom Action Research (PTK) approach. These instruments are written tests and observations. The results of the research were that in the first cycle of the first meeting, the percentage of students was 60.4% and in the second meeting of the first cycle, 63% was still in the low category, this was because students were faced with new situations in conveying what they still did not understand. In the second cycle of the first meeting the percentage result was 69% and in the second meeting of the second cycle it was 77% in the very good category. The conclusion of this research is that there is an increase in student learning outcomes by using Cooperative Talking Chips because students can learn independently and learn together, students can convey arguments using their own language and are able to complete the tasks given. Suggestions for teachers to make the Cooperative Talking Chips learning model an alternative worth considering in learning. Future researchers hope that this research can become a relevant reference with a wider scope.